2021
DOI: 10.3390/cells10010169
|View full text |Cite
|
Sign up to set email alerts
|

CD112 Regulates Angiogenesis and T Cell Entry into the Spleen

Abstract: Junctional adhesion proteins play important roles in controlling angiogenesis, vascular permeability and leukocyte trafficking. CD112 (nectin-2) belongs to the immunoglobulin superfamily and was shown to engage in homophilic and heterophilic interactions with a variety of binding partners expressed on endothelial cells and on leukocytes. Recent in vitro studies suggested that CD112 regulates human endothelial cell migration and proliferation as well as transendothelial migration of leukocytes. However, so far,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 41 publications
(40 reference statements)
1
18
0
Order By: Relevance
“…In CD112-deficient mice, the blood vessel coverage of the retina was significantly enhanced. A blockade of CD112 modulated EC migration and significantly enhanced tube formation [74]. Thus, changes in ECM composition and function are key modulators of the cellular microenvironment that impact various cellular pathologies and diseases.…”
Section: Ecm Remodeling By Cytoskeleton-related Proteins and Angioinf...mentioning
confidence: 99%
“…In CD112-deficient mice, the blood vessel coverage of the retina was significantly enhanced. A blockade of CD112 modulated EC migration and significantly enhanced tube formation [74]. Thus, changes in ECM composition and function are key modulators of the cellular microenvironment that impact various cellular pathologies and diseases.…”
Section: Ecm Remodeling By Cytoskeleton-related Proteins and Angioinf...mentioning
confidence: 99%
“…According to the topographical anatomy of EC, vascular and lymphatic endothelial cell exist. Several fundamental biological distinctions are present between lymphatic and blood EC despite the topographical similarities, more than 400 differences in the expressed genes, returning to the difference in the functions of each (Table 1) [39][40][41][42][43][44][45][46]. Lymphatic EC present semiprofessional antigen presentation to lymphatic circulatory T cytotoxic CD8 cells through an invadosome-shaped protrusion and express specific surface antigens and receptors such as podoplanin, vascular endothelial growth factor receptor-3 (VEGFR-3) or lymphatic vessel endothelial hyaluronan receptor-1 [47,48].…”
Section: Types Of Endothelial Cellsmentioning
confidence: 99%
“…Similarities and differences between VEC and LEC[39][40][41][42][43][44][45][46] Commonfeatures VEC LEC Barrier function, vasomotor tone, vascular permeability regulation, tissue vascularization, and immune response Regulation of coagulation Semi-professional antigen-presenting, B-cell homing to lymph nodes via CXCL13 expression Peroxisome proliferator-activated receptor delta H2S Surface receptor: G-coupled protein receptor, TLR 4, NLR, IL-10 receptor, sphingosine-1-phosphate and prostaglandins receptors, transient receptor potential, ephrin A, ephrin B2 and EphB4, neuropilins (accessory), Acetylcholine receptor (M1-5), Endoglin, scavenger receptors; CD36 (SR-B2) and SCARF-1 (SR-F1) Surface receptor: endothelial receptors FcRn, VEGFR2, vascular endothelial protein tyrosine phosphatase, receptor for vascular endothelial growth factor Flk1, receptor for sphingosine-1-phosphate 1, NLRP6, TGF-β receptor, Thromboxane A2 receptor, angiotensin II receptor (AT1), scavenger receptor class B type I, G proteincoupled receptor 68, histamine receptor (H1), tyrosine kinase Tie2 bradykinin receptor (B2), vitamin D endothelial receptor, albondin (gp60), FGFR2, serotonin receptor (S1), ET-1 receptor (ET-B), ADP and ATP receptor, DCC/neogenin and UNC5 receptors of netrin-1, Natriuretic peptide receptor A, B, and C Surface receptor: VEGFR-3, IL-1, IL12, IL18, IL27 receptors, C-type lectin receptor, Fc receptor (FCGR2B), LYVE-1, sigma receptor-1, Natriuretic peptide receptor D, scavenger receptors; MSR-1 (SR-A1), MARCO (SR-A6), STAB-2 (SR-H2), and CXCL16 (SR-G1) Released molecules: endothelin, prostacyclin I 2 , nitric oxide, urotensin, CNP, adenosine, purines, reactive oxygen species, H2S Induce angiogenesis by CD112 (nectin-2), netrin-1, FGF-2, TGF-β, TNF-α, IGF-1, and VEGF Released molecules: protein c and s, thrombomodulin, calmodulin, tissue-type plasminogen activator, plasminogen activator inhibitor type-I, plateletactivating factor, Von Willebrand factor, adrenomedullin MAFB transcription factor overexpressed MHC-II, H-2DMα, and H-2DMβ overexpression 208 difference in the expressed genes (NRCAM, TAGLN, www.acbjournal.org https://doi.org/10.5115/acb.22.098…”
mentioning
confidence: 99%
“…Moreover, it has been demonstrated that Nectin-2 is involved in the homecoming process of T-cell entry into the spleen. Both T-cell entry routes into the spleen (through the red pulp and the marginal zone) were impaired in the Nectin-2-deficient model [ 75 ].…”
Section: Nectins and Necls In Cancermentioning
confidence: 99%